2022
DOI: 10.1186/s12885-022-09643-9
|View full text |Cite
|
Sign up to set email alerts
|

Tescalcin promotes highly invasive papillary thyroid microcarcinoma by regulating FOS/ERK signaling pathway

Abstract: Background Part of papillary thyroid microcarcinoma (PTMC) has a high risk of tumor invasion and metastasis, which may occur in the regional lymph node metastasis or distant metastasis, severely threatening the life of patients. Invasion and metastasis are tightly involved in the proliferation, migration and invasion in cancer. This study aimed to investigate the role of tescalcin (TESC) in the proliferation, migration and invasion of PTMC. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…demonstrated that TESC promoted the PTMC progression by regulating the c-Fos expression related to ERK signaling pathway and detected the expression of EMT pathway-related indicators (E-cad, N-cad, Vimentin, Snail) (12), which are consistent with our results, though an ATC cell line was used.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…demonstrated that TESC promoted the PTMC progression by regulating the c-Fos expression related to ERK signaling pathway and detected the expression of EMT pathway-related indicators (E-cad, N-cad, Vimentin, Snail) (12), which are consistent with our results, though an ATC cell line was used.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, BRAF V600E mutation activated the ERK1/2 signaling pathway contributing to DTC dedifferentiation (28). Recently, it has been reported that TESC/FOS/ERK1/2 signaling axis was involved in the growth and metastasis of PTC cells (12). Our results showed that TESC high expression positively correlated with TDS of DTC.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…However, we did not observe similar results because only TLR-4 was activated; this could be attributed to the unique microenvironment of mechanical stretch in the expanded skin. Furthermore, S100A9 could interact with TLR-4 to promote cell growth [ 46 ], thereby influencing the activation of downstream transcription factors such as Jun [ 47 ] and Fos [ 48 ]. Because S100A9 has been shown to promote tissue ECM deposition via the TLR-4/ERK1/2 pathway during skin expansion, the downstream regulator may be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…TESC can also regulate cancer progression, and its abnormal expression is associated with various malignant tumors, including non-small cell lung cancer, liver cancer, gastric cancer, and colorectal cancer (8)(9)(10)(11). It has been reported that TESC promoted papillary thyroid microcarcinoma (PTMC) progression by regulating c-Fos expression, which may be related to the ERK signaling pathway (12). Another study con rmed that lncRNA ROR mediates the TESC/ALDH1A1/TUBB3/PTEN axis, thereby promoting the development of PTC (13).…”
Section: Introductionmentioning
confidence: 99%